Tax Decentralization – Approaches to Vertical Tax Revenue Structuring in the Public Sector - Nenkova, Presiana (Research Papers, 2021)
In local government budgets accrue revenues from various taxes, and the ability of local governments to influence the amount of the accumulated resources varies considerably. The main task of each of the approaches for vertical structuring of taxation in the public sector is to ensure an adequate level of funding for local public activities. At the same time, the design of local tax autonomy is crucial for the choice of policies at the local level and the fiscal and economic decisions made by local authorities. The aim of the present study is: first, to highlight the advantages and disadvantages of the three forms of tax decentralization – taxes imposed at the local level, tax base sharing and tax revenue sharing, and second, by examining international experience and vertical tax structures in OECD countries to reveal the extent to which the practice follows the conventional principles of tax decentralization. The results of the study show that the most widely used form of tax decentralization is one in which local authorities are given the opportunity to set tax rates for separate self-use or shared with other levels of governments tax base. Although tax revenue sharing as an alternative to subsidies is an attractive option for financing local public activities, its role is significantly more limited.